The Association Between Hypertension in Pregnancy and Preterm Birth with Fetal Growth Restriction in Singleton and Twin Pregnancy: Use of Twin Versus Singleton Charts - Kalafat, Erkan (J Clin Med, 2020)
Objective: To compare the rates of fetal growth restriction (FGR) in singleton and twin pregnancies using singleton and twin-specific birthweight standards. Methods: The study included liveborn twin and singleton pregnancies between January 2000 and January 2019. Hypertensive disorders of pregnancy (HDP) included gestational hypertension and pre-eclampsia. The study outcomes were FGR or small-for-gestational-age (SGA) at birth as assessed using singleton and twin reference charts. Results: The analysis included 1473 twin and 62,432 singleton pregnancies. In singleton pregnancies the risk of PTB <34 weeks without HDP (OR 2.82, p < 0.001), delivery ≥34 weeks with HDP (OR 2.38, p < 0.001), and PTB <34 weeks with HDP (OR 13.65, p < 0.001) were significantly higher in the pregnancies complicated by FGR compared to those without. When selective fetal growth restriction (sFGR) was assessed using the singleton standard, the risk of PTB <34 weeks without HDP (OR 1.03, p = 0.872), delivery ≥34 weeks with HDP (OR 1.36, p = 0.160) were similar in the pregnancies complicated by sFGR compared to those without, while the risk of PTB <34 weeks with HDP (OR 2.41, p = 0.025) was significantly higher in the pregnancies complicated by sFGR compared to those without. When sFGR was assessed using the twin-specific chart, the risk of PTB <34 weeks without HDP (OR 3.55, p < 0.001), delivery ≥34 weeks with HDP (OR 3.17, p = 0.004), and PTB <34 weeks with HDP (OR 5.69, p < 0.001) were significantly higher in the pregnancies complicated by sFGR compared to those without. The stronger and more consistent association persisted in the subgroup analyses according to chorionicity. The strength of association in dichorionic twin pregnancies resembles that of the singletons more closely and consistently when the FGR was diagnosed using the twin-specific charts. Conclusion: FGR in twin pregnancies has a stronger and more consistent association with HDP and PTB when using twin-specific rather than singleton charts. This study provides further evidence supporting the use of twin-specific charts when assessing fetal growth in twin pregnancies.